China’s national ETS: Global and local lessons - Jun Liu; Jiayin Hou; Qing Fan; Han Chen (Energy Reports, 2022)
Since July 16 2021, China’s national emissions trading scheme (ETS) has been officially launched. Comparing with the world’s major carbon markets, China’s carbon market is relatively immature and still needs further development and improvement. This paper lists global and local lessons to China’s national ETS, in terms of cap setting, permit allocation, MRV (Monitoring, Reporting, Verification), trading mechanism, implementation and so on. This article combines development experience with China’s national conditions to provide policy recommendations for the future construction of the national carbon market.